Desenvolvimento de sistema de baixo custo para medida do teor de umidade em solos não saturados baseado na técnica de Reflectometria no Domínio do Tempo - TDR - Somensi, Cauê Stocchi (2017)
The determination of moisture content is important in the design and construction stages of geotechnical works. The TDR - Time Domain Reflectometry technique stands out among the several methods for estimating the moisture content in unsaturated soils. The TDR tests present similar results to those determined through of the standard gravimetric method, with the advantage of promoting instantaneous measurements with non-destructive characteristics. In addition, they enable the portability and systems embedding. However, due to the its construction characteristics and working methodology, it considers a large number of variables, becoming complex and subject to inaccurate results. Currently, it is common the need for high investments for the acquisition of hardware and commercial software. The aim of the present work is the development of a low cost TDR system, including a control and analysis software. Features such as measurements by scheduling, automatic estimation of conductivity and moisture content. These estimates are made through calibration equation that can be provided to the software. Customized TDR probes have also been developed to work integrated with the proposed system, being manufactured with the 3D printing technology. Using solution with different concentrations of acetic acid, comparative tests were performed between the low cost TDR system and the TDR system formed by the TDR100 device and PC-TDR software, developed by Campbell Scientific Inc. The results show that with proper calibrations, the proposed system can be used for soil water content estimation in an efficiently and reliably way, with a standard error of the estimate of around 1%. The low cost TDR system was promising and could stimulate the use of TDR technique, increasing the alternatives of geotechnical testing apparatus in unsaturated soils.